2014
DOI: 10.1002/pmic.201300404
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome analysis of tracheal tissues in response to infectious bronchitis coronavirus, Newcastle disease virus, and avian influenza virus H9 subtype virus infection

Abstract: Infectious bronchitis coronavirus (IBV), Newcastle disease virus (NDV), and avian influenza virus (AIV) H9 subtype are major pathogens of chickens causing serious respiratory tract disease and heavy economic losses. To better understand the replication features of these viruses in their target organs and molecular pathogenesis of these different viruses, comparative proteomic analysis was performed to investigate the proteome changes of primary target organ during IBV, NDV, and AIV H9 infections, using 2D-DIGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…Vero cells were seeded in 24-well plates (Corning) and infected with each separate strain at an MOI of 1. In the adsorption and internalization stage, total RNA was extracted from the cells, before storing at −80°C for the subsequent quantification of viral loads, as described previously (Liu et al, 2006a;Sun et al, 2014). Three replicates were analyzed for each sample.…”
Section: Adsorption and Internalization Assay Using Real-time Rt-pcrmentioning
confidence: 99%
“…Vero cells were seeded in 24-well plates (Corning) and infected with each separate strain at an MOI of 1. In the adsorption and internalization stage, total RNA was extracted from the cells, before storing at −80°C for the subsequent quantification of viral loads, as described previously (Liu et al, 2006a;Sun et al, 2014). Three replicates were analyzed for each sample.…”
Section: Adsorption and Internalization Assay Using Real-time Rt-pcrmentioning
confidence: 99%
“…Emerging technologies, such as proteomic approaches, have become important tools for facilitating a comprehensive characterization of virus–host interactions involved in infection and pathogenesis . Several quantitative proteomics approaches have been used to provide specific insights into the gene expression profiles of coronaviruses including severe acute respiratory syndrome coronavirus (SARS‐CoV) , infectious bronchitis coronavirus , and transmissible gastroenteritis coronavirus . Generally, in host cells coronavirus infection gives rise to alterations in transcriptional patterns, the cell cycle, the cytoskeleton, apoptosis pathways, the immune system, stress responses, and likely also causes inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…La Sota is a lentogenic NDV strain that only replicates in the respiratory tract and induces no apparent clinical signs. In our previous work, we found that the expression of CG-1B was up-regulated in the trachea after infecting with La Sota at 7 and 12 dpi, while the presence of virus was undetectable since 12 dpi (25). The upregulation of CG-1B may contribute to the virus clearance, as we have clearly demonstrated that CG-1B can inhibit the adsorption and replication of NDV in vitro (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…So far, the contributions of host factors during the course of NDV infection remain largely unknown. Our previous proteomics analyses have shown that the abundance of chicken galectin (CG)-1B is up-regulated in the trachea of NDV-infected chickens, the primary target organ for this virus (25). In this study, we demonstrate for the first time that CG-1B directly bound to NDV and inhibited its hemagglutination (HA) activity in vitro.…”
mentioning
confidence: 72%
See 1 more Smart Citation